Distributed Model Predictive Cross-Dimensional Formation Control for Heterogeneous Multiagent Systems - Haitao Liu; Zhaoxin Li; Qingqun Mai; Haochun Liu; Xuehong Tian (IEEE Access)
In this paper, a distributed predefined-time model predictive formation control method is proposed for second-order multidimensional cross-dimensional heterogeneous multiagent systems (HMASs) with collision avoidance, switching topology and formation transformation. First, a distributed cross-dimensional formation control protocol based on the full or partial information of neighboring agents is proposed for multidimensional heterogeneous multiagent systems. Second, a formation cooperative control approach that can quickly achieve the desired formation and formation transformation is designed by combining the predefined-time control strategy with the auxiliary control law of Lyapunov-based distributed model predictive control (DMPC). In addition, collision avoidance among agents can be achieved by adding a collision penalty mechanism to the cost function. Finally, an application to heterogeneous multiagent unmanned surface vehicle and unmanned underwater vehicle (USV-UUV) systems, through which the effectiveness of the proposed results has been demonstrated, and the simulation results are analyzed to evaluate the effectiveness and reliability of the proposed method.